THE INFLUENCE OF LECTURER COMMUNICATION STYLE ON STUDENT UNDERSTANDING IN ONLINE LEARNING - Mahfud, Moh.; Zainullah, Zainullah (TOPLAMA, 2024)
This study aims to analyze the effect of lecturers' communication style on students' understanding in online learning, with a focus on verbal and non-verbal communication styles, the use of technology, and collaborative and adaptive approaches. The research method used is a quantitative approach with an explanatory research design. Data were collected through an online questionnaire completed by 200 students from various universities in Indonesia. Data analysis was performed using Structural Equation Modeling (SEM) and multiple linear regression to examine the relationship between lecturer communication style variables and student understanding. The results showed that verbal communication style had the most dominant influence on student understanding, with a contribution of 35%. Non-verbal communication style and the use of technology each contributed 20% and 25%, while collaborative and adaptive communication styles contributed 18% and 22%. These findings confirm that a combination of clear delivery of material, effective use of technology, and a collaborative and adaptive approach can significantly improve student understanding. However, this study also identifies challenges such as the limitations of online platforms in displaying non-verbal communication and the digital divide among students.